(Re-)Defining Disadvantage: Untouchability, Criminality and 'Tribe' in India, c. 1910s–1950s. (February 2020) - Gandee, Sarah
In contemporary India, the arena of identity politics and 'reservations' is highly contentious, with groups clamouring for official recognition within the categories of Scheduled Caste, Scheduled Tribe or Other Backward Class. This article sheds new light on the wider processes of inclusion and exclusion among these categories by delineating the contested position of the so-called 'criminal tribes' within this framework. Until the 1920s, these criminalized communities were generally positioned as a separate group alongside 'untouchable' and 'tribal' communities, each of which was considered to have faced particular forms of disadvantage which demanded certain protections and 'uplift'. Between the 1920s and 1950s, however, this distinct status was withdrawn amid debates over the boundaries, purpose and indeed responsibilities of representation within the evolving framework of group rights. While there was continued recognition of their distinct status in debates over definitions of disadvantage (in terms of a shared history of criminalization), this did not translate into official recognition as a separate category of disadvantaged citizen after independence, thereby complicating these communities' ability to access the preferential policies inaugurated by the independent constitution in 1950. The article challenges the idea that these political categories are innate or fixed, and simultaneously historicizes the demands of the denotified (ex-'criminal') and nomadic tribe movement, which today campaigns for a separate constitutional classification within the 'reservations' regime.